The Effects of Complete Decongestive Therapy on Breast Cancer Related Lymphedema - O.M. Baltag; A.I. Singuran; M. Apostu; M. Cordun (Editura Universitatii Transilvania din Brasov, 2023)
Breast cancer-related lymphedema is the most common side effect that occurs after the treatment. There are four stages of evolution of the lymphedema and the most frequent treatment used is complete decongestive therapy (CDT). This study aims to analyze the effectiveness of CDT in the treatment of breast cancer-related lymphedema. After the final assessment, the data were processed statistically and we found that the evaluated circumferences decreased, which demonstrated the effectiveness of the CDT.